2001
DOI: 10.1111/j.1553-2712.2001.tb01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Resident Patient Care Documentation Using a Hand‐held Computerized Device

Abstract: Abstract. Objective: To determine whether emergency medicine (EM) resident documentation of procedures, patient encounters, and patient follow-ups improved after implementation of a personal digital assistant (PDA) hand-held recording system. Methods: All first-year EM residents were provided a PalmV (Palm, Inc., Santa Clara, CA) PDA. A customized patient procedure and encounter program was constructed using Pendragon Forms (Pendragon Software Corporation, Libertyville, IL) and loaded into each PDA. Residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 6 publications
0
41
0
1
Order By: Relevance
“…We regularly observe medical house staff carrying hand-held devices, or personal digital assistants (PDAs), while on rounds, consulting with other staff, or writing patient summaries and this use is similar to previous reports [1][2][3][4][5][6][7][8][9][10][11][12]. At the time of this study, our institution's computerized hospital information systems included physician workstations, used primarily for order--entry and to access laboratory results, operative notes and other documentation.…”
Section: Introductionmentioning
confidence: 67%
“…We regularly observe medical house staff carrying hand-held devices, or personal digital assistants (PDAs), while on rounds, consulting with other staff, or writing patient summaries and this use is similar to previous reports [1][2][3][4][5][6][7][8][9][10][11][12]. At the time of this study, our institution's computerized hospital information systems included physician workstations, used primarily for order--entry and to access laboratory results, operative notes and other documentation.…”
Section: Introductionmentioning
confidence: 67%
“…Unsurprisingly, therefore, a substantial literature on organizations and technologies has documented the barriers that occur when a technology is introduced, and how these may be countered. For example, in a study of novel communication technology, Bird and Zarum (2001) concluded that successful innovation matched work tasks and satisfied user demands. Rosen and Gabbay (1999) found that managers were unimpressed by technical advantages, and evaluated a new technology in terms of its impact on the organization.…”
mentioning
confidence: 99%
“…33 Bird and coworkers found that the use of a handheld device was associated with an increase in first-year emergency medicine residents' documentation in three of 20 procedures. 34 The mean number of procedures, encounters and followups performed per resident using a handheld device was compared with a historical control group. It was concluded that the overall time savings in using a resident procedure database may result in a transition to a handheld computer-based procedure log.…”
Section: Medical Educationmentioning
confidence: 99%